A Study on the Novel ‘The God of Small Things’ By Arundhati Roy: Exploring the Impact of 'Love Laws' on Fraternal Twins' Lives (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The God of Small Things (1997)is the debut novel of Indian writer ArundhatiRoy. It is a story about the childhood experiences of fraternaltwins whose lives are destroyed by the "Love Laws" that laydown "who should be loved, and how. And how much." The book is adescription of how the small things in life affect people's behaviour and theirlives. The book won theBooker Prize in 1997.